2020
DOI: 10.1532/hsf.3059
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Hypothyroidism Increases the Requirement of Renal Replacement Therapy After Cardiac Surgery

Abstract: Background: Subclinical or biochemically diagnosed hypothyroidism (SCH) is defined as an elevated serum thyroid-stimulating hormone (TSH) with normal free thyroxine (FT4) levels. Thyroid hormones play a major role in the normal function of the heart and vascular physiology. Atherosclerosis, increased systemic vascular resistance, and decreased arterial compliance are common pathophysiological changes that may occur in hypothyroidism. Acute kidney injury (AKI) is one of the devastating complications after cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Such a discrepancy between renal supply and demand in O 2 and nutrients could predispose patients with hypoparathyroidism to the development of acute kidney injury. 75 A prolonged hypothyroid state could also provoke irreversible damage to the kidney. Population-based studies reveled the association between thyroid-stimulating hormone (increased during hypothyroidism) with higher prevalence of chronic kidney disease.…”
Section: Hypothyroidism and Renal Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a discrepancy between renal supply and demand in O 2 and nutrients could predispose patients with hypoparathyroidism to the development of acute kidney injury. 75 A prolonged hypothyroid state could also provoke irreversible damage to the kidney. Population-based studies reveled the association between thyroid-stimulating hormone (increased during hypothyroidism) with higher prevalence of chronic kidney disease.…”
Section: Hypothyroidism and Renal Functionmentioning
confidence: 99%
“…The subsequent activation of the tubule‐glomerular feedback triggers a more robust vasoconstriction of the preglomerular arterioles, exacerbating the already low blood supply. Such a discrepancy between renal supply and demand in O 2 and nutrients could predispose patients with hypoparathyroidism to the development of acute kidney injury 75 . A prolonged hypothyroid state could also provoke irreversible damage to the kidney.…”
Section: Thyroid Hormones and The Kidneymentioning
confidence: 99%
“…Our study is the first meta-analysis to evaluate the association between SCH and postoperative and long-term outcomes following cardiac surgery. The primary outcome was reported by 6 of the 7 retrospective studies that we analyzed, 18 , 19 , 23 , 25 , 26 , 28 and based on our analysis, SCH patients had a greater risk of operative mortality compared to their euthyroid counterparts. Although not surgery-related, other meta-analytic studies have been conducted focusing on cardiovascular outcomes, showing that SCH is associated with increased CHD and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported that impaired renal function is linked to both overt and subclinical hypothyroidism, which are associated with hypotension, increased vascular resistance, and decreased sodium reabsorption, which leads to volume contraction, reduced renal blood flow, and low glomerular filtration rate [4].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with advanced coronary artery disease (CAD) require a coronary artery bypass grafting (CABG). Some single-center retrospective clinical studies on the long-term prognosis of patients with hypothyroidism who underwent CABG have revealed a higher risk of revascularization, atrial fibrillation, and all-cause mortality [5][6][7] and increased risk of renal replacement therapy [4]. The exact physiology of thyroid disease and the relationship with post-CABG prognosis remain unclear.…”
Section: Introductionmentioning
confidence: 99%